2017
DOI: 10.1111/cas.13260
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress pathway PERKeIF2α confers radioresistance in oropharyngeal carcinoma by activating NF‐κB

Abstract: Endoplasmic reticulum stress (ERS) plays an important role in the pathogenesis and development of malignant tumors, as well as in the regulation of radiochemoresistance and chemoresistance in many malignancies. ERS signaling pathway protein kinase RNA‐like endoplasmic reticulum kinase (PERK)‐eukaryotic initiation factor‐2 (eIF2α) may induce aberrant activation of nuclear factor‐κB (NF‐κB). Our previous study showed that NF‐κB conferred radioresistance in lymphoma cells. However, whether PERK‐eIF2α regulates ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 38 publications
2
40
0
Order By: Relevance
“…Our previous results showed that ERS could regulate the phosphorylation of the radiation‐induced DNA DSB‐related protein ATM in oropharyngeal carcinoma . We hypothesized that XBP1 inhibition could increase radiosensitivity through the activation of DNA DSB formation.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Our previous results showed that ERS could regulate the phosphorylation of the radiation‐induced DNA DSB‐related protein ATM in oropharyngeal carcinoma . We hypothesized that XBP1 inhibition could increase radiosensitivity through the activation of DNA DSB formation.…”
Section: Resultsmentioning
confidence: 96%
“…We previously demonstrated that EGFR confers radioresistance in HPV‐negative human oropharyngeal carcinoma by activating ERS signaling through the double‐stranded RNA‐activated protein kinase‐like ER kinase (PERK) and inositol‐requiring enzyme 1 alpha (IRE1α). Our further research found that PERK confers radioresistance by activating the inflammatory cytokine, nuclear factor‐κB (NF‐κB) . Madhuri C et al showed that IRE1 could induce autophagy in murine macrophage cells under irradiation .…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Similarly, the IRE1 axis also stimulates NF-κB activity by enforcing proteasomal degradation of IκB (Duran-Aniotz et al, 2017;Rubio et al, 2011;Tam et al, 2012). PERK commands a slightly different pathway for this purpose, it enforces translational inhibition of IκB thereby freeing NF-κB for engaging its transcriptional program (Blais et al, 2006;Halliday et al, 2017;Pytel et al, 2016;Qiao et al, 2017;Tam et al, 2012). Lastly, although ATF6 axis has been shown to influence NF-κB activation yet, the exact mechanism underlying this cascade has not been established (Tam et al, 2018;Yamazaki et al, 2009).…”
Section: Er Stress-induced Inflammationmentioning
confidence: 99%